FORAMINIFERAL DISTRIBUTIONS AS PROXY TO DETERMINE ITF VARIABILITY IN HALMAHERA SEA - Gustiantini, Luli
Indonesian Troughflow is a marine current that bring marine water mass from Pacific Ocean to Indian Ocean through the Indonesian waters. ITF is a part of thermohaline circulation, which is a global water movement that carries cold currents from Northern Atlantic Ocean to the Pacific Ocean and Indian Ocean through Indonesian Waters. The intensity of ITF affects to the rainfall intensity in Indonesian area, therefore understanding ITF is important in order to make a preventive action to anticipate the extreme climate. Foraminifera is a very sensitive microfauna to the environmental changes. So many studies have been conducted using this microfauna as a proxy to reconstruct paleoclimate. Therefore, the purpose of this study is to analyze the variability of ITF by using foraminifera. Based on calibration to isotope stratigraphy, the sediment of core MD10-3339 has been deposited since 64210 BP. The core is consists of grey clay that abundant with foraminiferal test. Based on cluster analysis, the core can be divided into 5 biozones, with dominant species are Bulimina, Bolivina, Uvigerina, Bolivinita quadrilatera, from benthic, and the planktonic is dominated by Globigerinoides ruber, Neogloboquadrina dutertrei, Globigerina bulloides, and Pulleniatina obliqueloculata. The interval core studied is deposited in the bathyal setting which is characterized by 90% of PB ratio and the average of index diversity is higher than 3. Generally, ITF intensity was stronger during glacial compared with that during interglacial. Weaker ITF is characterized by higher temperature, deeper thermocline, low salinity, and low intensity of bottom current, and occurred during intervals of 3000 – 2940 cm (64210 – 63310 BP), 2490 – 2460 cm (53950 – 53360 BP), 2280 - 2250 cm (47470 – 46540 BP), 2040 – 1950 cm (42060 - 40600 BP), 1590 – 1530 cm (34000 – 33000 BP), 1230 – 1200 cm (22920 – 21000 BP), 1110 – 1080 cm (19410 – 19000 BP), 780 – 690 cm (13320 – 11820 BP), 570 – 510 cm (11000 – 9090 BP), 330 – 270 cm (4720 – BP), and 90 - 30 cm (2140 – 1950 BP). These occurrences were coincided with HE 6 – HE 4, HE 2, LGM, and during the climate changes between glacial - interglacial. The intensity of ITF in the study area was also influenced by monsoon. During glacial Southeast Monsoon the intensity was stronger indicated by thinner mixed layer, lower temperature, higher productivity, and shallower thermocline. Furthermore, Northwest Monsoon was stronger during Interglacial reflected by warmer temperature, lower productivity, deeper thermocline, thicker mixed layer, and lower salinity.